Examining the Potential of Inuit Art and Artistic Processes to Facilitate Knowledge System Bridging About Environmental Change - Rathwell, Kaitlyn (University of Waterloo, 2016)
Art and artistic processes have an important role to play to bridge knowledge systems about environmental change and to inform governance action. Inuit and western knowledge systems contribute to understanding and governance of Arctic sea ice in Canada. Siku, sea ice in Inuktitut, connects to Inuit identity and well-being via multiple dimensions, including for example, food security, mythology and origin stories, travel and mental health. Increasingly complex and unprecedented changes in Arctic sea ice, driven by global climate change, presents challenges for local communities and their efforts to respond to those changes. Of utmost importance is to build bridges between Indigenous and scientific knowledge systems to enhance decision making about environmental change, such as Arctic sea ice change, as well as between generations of Indigenous knowledge holders to maintain social-ecological resilience. Six months living in Pangnirtung and Cape Dorset, Nunavut, Canada enabled an embodied experience and the collection of rich qualitative data upon which this dissertation is based. Knowledge systems bridging is defined here as connecting two or more knowledge systems to arrive at novel insights about phenomena, and in ways that nurture the integrity of each participating knowledge system. In this dissertation, I demonstrate that art and artistic processes have an important role to play in the creation of compelling settings to respectfully bridge knowledge systems. In doing so, I provide a qualitative analysis that strengthens global understandings of how artistic approaches can enhance bridging diverse knowledge systems about environmental change and governance. To study how artworks and artistic processes facilitate bridging knowledge systems, I used complementary data collection techniques. A systematic literature review provided the foundation for a typology of settings that are used in the environmental change governance literature to bridge indigenous and scientific knowledge systems. Semi-structured ...